"A Little Is Better Than Zero" or "Pay Enough or Don't Pay at All"? Evidence on the Size of Pay-for-Performance Across the Sectors. (June 2018) - Chen, Chung-An
Regarding the effect of pay-for-performance (PFP), standard economic reasoning suggests that "a little is better than zero, " meaning that even small performance payments can improve employees' work morale. An alternative view, "pay enough or don't pay at all, " suggests that paying too little may instead erode employees' work morale. Using the U.S. General Social Survey (GSS) data, the present study finds evidence that the two views actually complement each other: Small payments can improve employees' work effort (e.g., working hours), but can also potentially compromise their work attitudes (e.g., job satisfaction). In addition, employees in different working sectors may have different understanding of what "small size" really means. Findings are followed by theoretical and practical implications.